2011
DOI: 10.4081/gh.2011.164
|View full text |Cite
|
Sign up to set email alerts
|

Predicting risk habitats for the transmission of the small liver fluke, Dicrocoelium dendriticum to grazing ruminants

Abstract: Abstract. A multiple regression model was used to analyse if the structure of vegetation and soil patches in grazed units (pastures) can be used as explanatory variables to predict the prevalence of Dicrocoelium dendriticum, a common parasite of cattle and sheep, in grazing cattle stocks on the Baltic island of Öland in southern Sweden. The scale dependency was evaluated by comparing three levels of spatial resolution of patches. Prevalence data were obtained from slaughtered animals. Our models predict that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…As a result, the area surrounding the CREMOPAR is overrepresented as compared to other sampled areas. This should not be confused with a clustered distribution pattern of this parasite, as reported in other studies [4,6,11,29] where clustered areas of presence were observed within larger sampled, but negative, areas. In these surveys, the clustering observed was likely due to the specific eco-climatic condition required by intermediate hosts of D. dendriticum to develop.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…As a result, the area surrounding the CREMOPAR is overrepresented as compared to other sampled areas. This should not be confused with a clustered distribution pattern of this parasite, as reported in other studies [4,6,11,29] where clustered areas of presence were observed within larger sampled, but negative, areas. In these surveys, the clustering observed was likely due to the specific eco-climatic condition required by intermediate hosts of D. dendriticum to develop.…”
Section: Discussionsupporting
confidence: 81%
“…Dicrocoeliosis is also zoonotic [22,36]. Hence, modelling the spatial distribution of this parasite can help to improve its management in higher risk regions [11,27]. Due to global climate change, seasonal and spatial patterns of parasites can alter [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results suggest that these factors play a key role in the development, survival and transmission of Dicrocoelid flukes and their intermediate hosts. The results also found a high correlation between distance from population built-up areas and summer NDVI and the presence of Dicrocoelium infection, explained by the observation that forest areas with permanent pastures, good water availability and suitable soil type provide suitable habitats for land snails and ant intermediate hosts, and opportunities for final host infection [37].…”
Section: Discussionmentioning
confidence: 76%
“…Also, the longevity of infective miracidia in the environment, (Alunda and Rojo-Vàzquez, 1983); the role of sympatric wildlife as reservoir hosts; and a broader consideration of the relationship between changing environmental and climatic conditions and parasite epidemiology (Ekstam et al, 2011).…”
Section: Introductionmentioning
confidence: 99%